THE INTERNAL FACTORS AFFECTING THE FINANCING OF SHARIA GENERAL BANK IN INDONESIA FOR 2014-SEPTEMBER 2019 PERIOD - Dinayatin Umaroh; Siti Zulaikha (Universitas Airlangga, 2020)
This study aims to determine the effect of internal factors of Islamic commercial banks in Indonesia on financing. Measured through Bank Size (Size), Liquidity Ratio, Capital Ratio, and Third Party Funds (DPK) of the four independent variables will be tested for the effect on one dependent variable. Sampling in this study uses a purposive sampling technique that includes all Islamic commercial banks in Indonesia and is taken in accordance with the criteria and research objectives into the observation data. The observation period of research data from 2014-September 2019 amounted to 8 banks. The analytical method used is panel data regression. The results of this study found that partially Bank Size, Liquidity Ratios, Capital Ratios and Third Party Funds had a positive and significant effect on Islamic commercial bank financing in Indonesia. However, the Capital Ratio has a negative and significant effect on Islamic commercial bank financing in Indonesia. Simultaneously, the four variables indicate that the independent variable influences the financing of Islamic commercial banks. The significance value of the F-statistic test shows the number 0.000000 with the value of the R-squared coefficient 0.990219 or 99% which means the four independent variables can explain financing well.Keywords: Financing, bank size, liquidity ratio, capital ratio, third party fundsREFFERENCE Ajija, S. R., Sari, D.W., Setianto, R. H., & Primanti, M. R. (2011). Cara cerdas menguasai Eviews. Jakarta: Salemba Empat.Ansari, L. P. (2017). Pengaruh tingkat inflasi dan dana pihak ketiga terhadap pembiayaan dan implikasinya terhadap pendapatan pada bank umum syariah di indonesia (studi kasus bank syariah bukopin). Jurnal E-KOMBIS, 3(7), 93–103.Arisandi, L.W., Desak, N.S.W., & Edy, S. (2015). Pengaruh Kondisi Internal Capital Adequacy Ratio, Loan to Deposit Ratio,dan Performing Loan pada Keputusan Pemberian Kredit di PT bank Rakyat Indonesia (Persero) Tbk Tahun 2004-2013. Jurnal Ilmiah Mahasiswa Akuntansi Undiksha, 3(1).Arnan, S. G., & Kurniawasih, I. (2014). Pengaruh jumlah dana pihak ketiga dan tingkat non- performing financing terhadap pembiayaan. Proceedings SNEB 2014, 1, 1–6.Aziza, R. V. S., & Mulazid, A. S. (2015). Analisis pengaruh dana pihak ketiga, non performing financing, capital adequacy ratio, modal sendiri dan marjin keuntungan terhadap pembiayaan murabahah. Jurnal Ekonomi Dan Bisnis Islam, 2(1), 1–15.Fauzan, M. (n.d.). Pengaruh dana pihak ketiga dan modal sendiri terhadap pembiayaan. JII, 2(1), 1–20.Gianni, Nur Gilang. (2013). Faktor yang mempengaruhi pembiayaan mudharabah pada bank umum syariah di Indonesia. Accounting Analysis Journal,2(1), 96-103.Gujarati, D.N., & Zhu, L. (2004). Basic econometrics, fourth edition. New York: Mc Graw-Hill Comprnies. Gunanto. D. S. dkk. 2018. Pengaruh Financing to Deposit Ratio (FDR), Dana Pihak Ketiga (DPK), dan Return On Asset (ROA) terhadap pembiayaan musyarakah. Jurnal Ilmiah Edunomika, 2(2), 219-230.Husaeni, U. A. (2017). Determinan pembiayaan pada bank pembiayaan rakyat syariah di Indonesia. Esensi, 7(1), 49–62. https://doi.org/10.15408/ess.v7i1.4542Ichsan, Nurul. (2013). Pengelolaan likuiditas bank syariah. Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah. 6(1), 82-103.Ismail, Rifki. (2011). The Indonesian Islamic banking theory and practices. Jakarta: Gramata Publishing.Karim, A. A. (2010). Bank islam (analisis fiqih dan keuangan). Jakarta: PT. Raja Grafindo Persada.Kasmir. (2014). Analisis laporan keuangan. Jakarta: PT Raja Grafindo Persada.Kumara, Melany Devinta. (2017). Pengaruh bank size dan portofolio kredit terhadap resiko kredit bermasalah. Skripsi tidak diterbitkan. Surabaya: Fakultas Ekonomi dan Bisnis Universitas Airlangga.Kurnia, Indra dan Wisnu Mawardi. (2012). Analisis Pengaruh BOPO, EAR, LAR dan firm size terhadap kinerja keuangan (studi kasus pada bank umum konvensional yang terdaftar di Bursa Efek Indonesia Periode 2008-2011). Diponegoro Journal of Management, 1(4), 49-57.Kurniawanti, A., & Zulfikar. (2014). Analisis faktor-faktor yang mempengaruhi volume pembiayaan berbasis bagi hasil pada bank umum syariah di Indonesia. Seminar Nasional dan Call For Paper. 145-164.Malede, Mitku. (2014). Determinants of commercial banks lending: evidence from Ethiopian Commercian Bank. European Journal of Business and Management, 6, 109-118.Muhammad. (2005). Manajemen bank syariah. Yogyakarta: UPP AMP YKPN.Muhammad. (2014). Manajemen dana bank syariah. Jakarta: Raja Grafindo Persada.Nurhalimah. T. P. (2005). Analisis faktor-faktor yang mempengaruhi pembiayaan bank syariah dalam upaya pengembangan usaha kecil di Sumatra Utara. Skripsi tidak diterbitkan. Medan: Universitas Sumatra Utara.Nurhasanah, L. (2009). Pengaruh kas, dana pihak ketiga, SWBI (Sertifikat Wadiah Bank Indonesia), marjin keuntungan, dan NPF (Non Performing Financing) terhadap pembiayaan murabahah. Skripsi tidak diterbitkan. Yogyakarta: Universitas Muhammadiyah Yogyakarta.Octavina. K. dan emile. S. D. (2012). Pengaruh kas, bonus SWBI (Sertifikat Wadiah Bank Indonesia), marjin keuntungan, dan dana pihak ketiga terhadap pembiayaan murabahah: Studi empiris pada bank umum syariah di Indonesia. Jurnal akuntansi & Investasi, 13(1), 53-67.Olokoyo, Felicia Omowunmi. (2011). Determinants of commercial bank lending behaviour in Nigeria. Intenational Journal of Financial Research, 2, 61-72.Pratin., dan A. Adnan. (2005). Analisis Hubungan simpanan, modal sendiri, npl, prosentase bagi hasil, dan markup keuntungan terhadap pembiayaan pada perbankan syariah studi kasus pada Bank Muamalat Indonesia (BMI). Kajian Bisnis dan Manajemen. Edisi Khusus on Finance, 35-52.PT Bank Mega Syariah. (2019). Laporan Triwulanan. Diakses pada 3 Januari 2020. https://www.megasyariah.co.idPT Bank Muamalat Indonesia. (2019). Laporan Triwulanan. Diakses pada 3 Januari 2020. https://www.bankmuamalat.co.idPT Bank Syariah Bukopin. (2019). Laporan Triwulanan. Diakses pada 3 Januari 2020. https://www.syariahbukopin.co.idPT Bank Syariah Mandiri. (2019). Laporan Triwulanan. Diakses pada 3 Januari 2020. https://www.mandirisyariah.co.idPT BCA Syariah. (2019). Laporan Triwulanan. Diakses pada 3 Januari 2020. https://www.bcasyariah.co.idPT BNI Syariah. (2019). Laporan Triwulanan. Diakses pada 3 Januari 2020. https://www.bnisyariah.co.idPT BRI Syariah. (2019). Laporan Triwulanan. Diakses pada 3 Januari 2020. https://www.brisyariah.co.idPT Maybank Syariah. (2019). Laporan Triwulanan. Diakses pada 3 Januari 2020. https://www.maybanksyariah.co.idPurwanto, Rakhmat dan Endang Tri Widyarti. (2011). Analisis perbandingan efisisensi Bank Umum Konvensional (BUK) dan Bank Umum Syariah (BUS) di Indonesia dengan metode Data Envelopment Analysis (DEA) (Perode 2006-2010). Skripsi tidak diterbitkan. Semarang: Universitas Diponegoro.Qoyum, Abdul. (2010). Equity based financing policy, capital adequacy ratio discriminant and Islamic bank financing insurance corporation. Thesis. Kuala Lumpur: International Islamic University Malaysia.Schaik, D. (2001). Islamic banking. The Arab Bank Review, 3(1), 45-52.Safitri, I., Nadirsyah, N., & Darwanis, D. (2016). Pengaruh kinerja keuangan terhadap pembiayaan bank umum syariah di Indonesia (periode 2009-2013). Share - Jurnal Ekonomi Dan Keuangan Islam, 5(2), 155–164. https://doi.org/10.22373/share.v5i2.1239Siregar. N. (2005). Analisis faktor-faktor yang mempengaruhi penyaluran dana perbankan syariah di Indonesia. Skripsi tidak diterbitkan. Medan: Universitas Sumatra Utara.Umam, Khaerul. (2013). Manajemen perbankan syariah. Bandung: CV. Pustaka Setia.Verbeek, M. (2008). A guide to modern econometrics. New York: John Wiley & Sons.Wahyu, D. R. (2016). Financing To Deposit Ratio (FDR) sebagai salah satu penilaian kesehatan bank umum syariah (studi kasus pada bank BJB syariah cabang Serang). Jurnal Ekonomi Keuangan dan Bisnis Islam, 7(1), 19-36.Widarjono, Agus. (2013). Ekonometrika: Pengantar dan aplikasinya disertai panduan Eviews. Yogyakarta: UPP STIM YKPN.Zulkhibri, M. (2018). The impact of monetary policy on Islamic bank financing: bank-level evidence from Malaysia. Journal of Economics, Finance and Administrative Science, 23(46), 306–322. https://doi.org/10.1108/JEFAS-01-2018-0011